A Framework to Identify Antigen-Expanded T Cell Receptor Clusters Within Complex Repertoires - Ceglia, Valentina; Kelley, Erin J.; Boyle, Annalee S.; Zurawski, Sandra; Mead, Heather L.; Harms, Caroline E.; Blanck, Jean-Philippe; Flamar, Anne-Laure; Kirschman, Jung Hwa; Ogongo, Paul; Ernst, Joel D.; Levy, Yves; et al. (Frontiers in Immunology, 2021)
Common approaches for monitoring T cell responses are limited in their multiplexity and sensitivity. In contrast, deep sequencing of the T Cell Receptor (TCR) repertoire provides a global view that is limited only in terms of theoretical sensitivity due to the depth of available sampling; however, the assignment of antigen specificities within TCR repertoires has become a bottleneck. This study combines antigen-driven expansion, deep TCR sequencing, and a novel analysis framework to show that homologous ‘Clusters of Expanded TCRs (CETs)’ can be confidently identified without cell isolation, and assigned to antigen against a background of non-specific clones. We show that clonotypes within each CET respond to the same epitope, and that protein antigens stimulate multiple CETs reactive to constituent peptides. Finally, we demonstrate the personalized assignment of antigen-specificity to rare clones within fully-diverse uncultured repertoires. The method presented here may be used to monitor T cell responses to vaccination and immunotherapy with high fidelity.